Wsparcie psychopedagogiczne rodziny dziecka w cierpieniu wszechogarniającym realizowane w warunkach hospicyjnych - Godawa, Grzegorz (Analecta Cracoviensia, 2011)
The comprehensive suffering starts when the pain paralyzes not only the body but also particular forms of human activity. The suffering affects the ill person as well as their environment. It is especially severe for a family with a terminally ill child. Hence, the family often expects help from professionals. Psychopedagogical support of the ill child and its family implemented in a hospice environment embraces several spheres of the family functioning, e.g. the activity aimed at reformulation of the family goals, a response to the healthy siblings’ needs, strengthening of marital bonds and support in mourning.